FENOMENA JASA TITIP (JASTIP) DAN POLEMIK BAGI KELANGSUNGAN PRODUK UMKM - Anggit Dyah Kusumastuti (Universitas Sahid Surakarta, 2020)
Entrusted services or in the term personal shopper is a work in and out of shops, malls or large traders with the aim of buying goods or brands ordered by customers in accordance with their wishes. The goods sought are not only at the local level but there is also a demand for goods from abroad. In the midst of the dominance of the online shop business, the presence of business services entrusted can still generate profits for actors and still attract consumer interest. The rapid development of technology, the widespread use of social media, as well as the consumptive nature of Indonesian society is behind the growing interest of the community in doing jastip business. The purpose of this study was to determine the development of entrusted services and the impact caused by jastip's behavior for the sustainability of MSME products. The research method is a library study method. Data obtained from scientific books, research reports, regulations, provisions, annual books, and written sources both print and electronic. The results of the study note that the development of entrusted services through internet media has begun to mushroom in Indonesia so that it is well known and can be well received by all members of the community. This jastip phenomenon is currently being targeted by the government to be able to increase state revenue through the tax on jastip goods. The jastip business goods are taxed on average around 25-27 percent. However, the jastip business polemic arises because it involves foreign imported products related to the determination of customs. Besides the polemic that occurred related to the survival of MSME products because the product still received less attention and was exposed to its existence by the community.